The World According to Bob: Two Days of Music and Talks around the Work of Bob Gilmore - Smalt, Elisabeth; Ozzard, Patrick; Denyer, Frank (2016)
Bob Gilmore's presence on the new music scene radiated a unique combination of energy, openness, excitement, critical insight, sympathy and humour. His outstanding biographies of Harry Partch and Claude Vivier, and his musicological and other writings were complemented by passionate and informed advocacy of an extraordinary range of composers and music of recent times. Much of the music he embraced and wrote about was radically new and highly individual. Latterly, performing and commissioning with Trio Scordatura, he became directly involved in creating the work he loved. It was clear, following his death in January 2015, that many musicians feel his work and its implications deserve serious and more widespread recognition. In The World according to Bob, we hope to encourage that recognition by engaging with his achievements and what they mean for music, musical biography, history and musicology, and also to ask how Bobs legacy might be passed on for the future.
Keywords: 20th Century (1901-2000); Biography